Activity of glucose-6-phosphate dehydrogenase (G6PD) in newborns in a public hospital in the city of Campina Grande, State of Paraíba, Brazil (Research, Society and Development, 2020)
In glucose 6 phosphate dehydrogenase (G6PD) deficient erythrocytes, the decrease in the reduction of NADP in NADPH, leads to a low reducing potential that interferes with the oxidative metabolic capacity of the organism, being vulnerable to hemolysis, with oxidation of the globule membrane, which can lead to the hemolytic crisis. The manifestations of G6PD deficiency are triggered by environmental factors such as drugs, beans, infections. Clinical manifestations consist of hemolytic crisis and neonatal jaundice. Studies indicate that in Brazil the prevalence of G6PD is around 1 to 10%, with the highest rates in populations with African ancestry. The objective was to investigate the G6PD deficiency in newborns in a public maternity hospital in the city of Campina Grande. This is a cross-sectional study, where umbilical cord blood was collected from 147 newborns. The diagnosis of G6PD deficiency will be carried out through the methaemoglobin reduction test (Brewer's test). The city of Campina Grande, as well as the entire Borborema Compartment, does not present any data regarding the prevalence of G6PD deficiency. Through the SUS, the Ministry of Health strengthens the collection of information related to this disease with a view to implementing a health care program for detected patients, promoting improvements in their quality of life.